Justification of invasiveness criteria for alien plant species in Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
Eleven characters that characterize potential invasiveness of species or their populations are suggested as the criteria to assess the risk of alien species phytoinvasion. This study is based both on the analysis of the invasive plants’ features in Ukraine and a number of literature sources.
Keywords: invasive alien plants, invasiveness criteria.